2013
DOI: 10.4067/s0718-40262013000100015
|View full text |Cite
|
Sign up to set email alerts
|

Cómo valorar e interpretar un artículo sobre pronóstico

Abstract: How to assess and interpret a prognostic studyPrognosis is the prediction of the evolution of a given disease or event of interest and the frequency of occurrence of specific outcomes. The ideal study design to assess prognosis are cohort studies. However many prognostic studies have case-control or case series designs. Prognostic studies should include all participants with the event of interest of a determinate geographical region, to avoid bias. The measurement precision and exactitude of intervening variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…Although the risk of this bias appearing is intimately linked to clinical research 18 , few researchers are aware of the biases from which they may suffer. The most well-known selection biases are Berkson's or Neymann's bias, among others 19,20 , but there are other groups such as information, measurement, etc., which were not mentioned. Regarding this, one study showed that out of 704 articles, only 514 (73%) had the help of an expert in methodology and statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of this bias appearing is intimately linked to clinical research 18 , few researchers are aware of the biases from which they may suffer. The most well-known selection biases are Berkson's or Neymann's bias, among others 19,20 , but there are other groups such as information, measurement, etc., which were not mentioned. Regarding this, one study showed that out of 704 articles, only 514 (73%) had the help of an expert in methodology and statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of this bias appearing is intimately linked to clinical research [22], few researchers are aware of the biases from which they may suffer. The most well-known selection biases are Berkson's or Neymann's bias, among others [23,24], but there are other groups such as information, measurement, etc., which were not mentioned. Regarding this, one study showed that out of 704 articles, only 514 (73%) had the help of an expert in methodology and statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Constituye información relevante para el paciente y sus familiares, y es indispensable al momento de plantear opciones terapéuticas y planificar adecuadamente la administración de recursos 17 . El principal factor pronóstico a considerar en adenocarcinoma de páncreas es el grado de avance de la enfermedad al momento del diagnóstico, lo que condiciona a su vez la opción de tratamiento curativo, cual es la cirugía 7 .…”
Section: Discussionunclassified